Risk estimates and features of infectious events in subjects with different causes and level of neutropenia - Manuli, E.; Intra, J.; Limonta, G.; Brambilla, P. (International Journal of Research in Medical Sciences, 2019)
Neutropenia is diagnosed when absolute neutrophil count (ANC) is less than 1,500 cells/µL.1 Specific causes and severity of neutropenia were directly related to the risk of infection. Four decades ago, Bodey et al. demonstrated an inverse relationship between neutrophils number and infection in subjects affected by acute leukemia after chemotherapy.2 The risk of infection increased when ANC was less than 500 cells/µL for a long period, whereas it is decreased when ANC is greater than 500 cells/µL and the duration of neutropenia is reduced.